2019
DOI: 10.1007/s11676-019-01041-5
|View full text |Cite
|
Sign up to set email alerts
|

Douglas-fir climate sensitivity at two contrasting sites along the southern limit of the European planting range

Abstract: further common garden experiments should test adaptation and the interaction between genetics and environment of second-or third-generation seeds from old stands across Europe such as done by the old International Union of Forest Research Organizations (IUFRO) or the European Douglasfir Improvement Research Cooperative (EUDIREC) experimentation programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 75 publications
0
16
0
Order By: Relevance
“…As example, Casalegno et al [99] indicated an increment of spatial distribution of Arolla pine as consequence of the progressive abandonment of pastures in the Alps. Instead, Douglas fir is indicated as a tolerant species versus drought events [100,101] and its habitat suitability is indicated in increment in Europe in future time periods by Dyderski et al [102]. In the end, laricio pine is indicated as tolerant to heat and drought events [103].…”
Section: Sdm As a Tool For Forest Management Options In The Italian Fmentioning
confidence: 99%
“…As example, Casalegno et al [99] indicated an increment of spatial distribution of Arolla pine as consequence of the progressive abandonment of pastures in the Alps. Instead, Douglas fir is indicated as a tolerant species versus drought events [100,101] and its habitat suitability is indicated in increment in Europe in future time periods by Dyderski et al [102]. In the end, laricio pine is indicated as tolerant to heat and drought events [103].…”
Section: Sdm As a Tool For Forest Management Options In The Italian Fmentioning
confidence: 99%
“…As example, Casalegno et al (2010) indicated an increment of spatial distribution of Arolla pine as consequence of the progressive abandoned of pastures in the Alps. Instead, Douglas r is indicated as tolerant species versus drought events (Vitali et al 2017;Castaldi et al 2019) and its habitat suitability is indicated in increment in Europe on future time period by Dyderski et al (2018). In the end, laricio pine is indicated as tolerant to heat and drought events by Cheaib et al (Cheaib et al 2012).…”
Section: Sdm As a Tool For Forest Management Options In The Italian Fmentioning
confidence: 99%
“…The national or local experimental programs were established in many European countries, from Spain to Bulgaria and from Northern France to Southern Italy [ 5 ]. Seeds were often collected independently from the native range, mainly according to local climate and expert knowledge [ 12 ]. Therefore, many planted forests were realized using the most promising genotypes (i.e., seed sources) which were cultivated for timber and to generate new seeds for planting.…”
Section: Introductionmentioning
confidence: 99%
“…This information is only partially known but results were very promising, showing that the second-generation seeds were often able to overcome the growth performances of native ones [ 13 ]. Unfortunately, despite the interesting scientific evidence, such results remain partially obscured by the lack of knowledge concerning the genotypes used in the first “independent” and country-level experimentation of Douglas-fir [ 12 , 14 ]. Therefore, relating the performance in the native with that in the introduced zones is generally hard and a real genotype–environment–performance assessment has rarely been conducted [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation